Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Moral dan Etika Siswa di SMK Negeri 4 Batam - Afi Parnawi; Dian Ahmed Ar Ridho (Journal on Education, 2023)
The teacher is an important figure in the world of education and has the main task of teaching and educating students to become human beings who are educated, moral and have good ethics. Islamic religious education is one of the subjects that teaches students about morals and ethics, especially in the perspective of social life. Morals and ethics are important instruments that must be owned by every human being, especially students who are new to and learn about them. An Islamic religious education teacher as a professional in the field of religion, at least has the main task of being a teacher, educator and guide for students. Moral and ethics are the main goals of learning for Islamic religious education teachers, because when they are still in school, it is easier for students to form and instill good values regarding morals and ethics. Allah SWT, the Lord of the universe, has created reason and lust in humans, so this shows that every human being is inseparable from goodness and error. So the role of an Islamic Religious Education teacher is needed in an effort to improve student morals and ethics.